Data-independent acquisition proteomics reveals circulating biomarkers of coronary chronic total occlusion in humans - Li, Jun; Jiang, Xue-Jun; Wang, Qun-Hui; Wu, Xing-Liang; Qu, Zhe; Song, Tao; Wan, Wei-Guo; Zheng, Xiao-Xin; Yi, Xin (Frontiers in Cardiovascular Medicine, 2022)
Introduction The pathophysiology of coronary chronic total occlusion (CTO) has not been fully elucidated. Methods In the present study, we aimed to investigate the potential plasma biomarkers associated with the pathophysiologic progression of CTO and identify protein dynamics in the plasma of CTO vessels immediately after successful revascularization. We quantitatively analyzed the plasma proteome profiles of controls (CON, n = 10) and patients with CTO pre- and post- percutaneous coronary intervention (PCI) (CTO, n = 10) by data-independent acquisition proteomics. We performed enzyme-linked immunosorbent assay (ELISA) to further confirm the common DEPs in the two-group comparisons (CON vs. CTO and CTO vs. CTO-PCI). Results A total of 1936 proteins with 69 differentially expressed proteins (DEPs) were detected in the plasma of patients with CTO through quantitative proteomics analysis. For all these DEPs, gene ontology (GO) analysis and protein-protein interaction (PPI) analysis were performed. The results showed that most of the proteins were related to the negative regulation of proteolysis, regulation of peptidase activity, negative regulation of hydrolase activity, humoral immune response, and lipid location. Furthermore, we identified 1927 proteins with 43 DEPs in the plasma of patients with CTO vessels after immediately successful revascularization compared to pre-PCI. GO analysis revealed that the above DEPs were enriched in the biological processes of extracellular structure organization, protein activation cascade, negative regulation of response to external stimulus, plasminogen activation, and fibrinolysis. More importantly, we generated a Venn diagram to identify the common DEPs in the two-group comparisons. Seven proteins, ADH4, CSF1, galectin, LPL, IGF2, IgH, and LGALS1, were found to be dynamically altered in plasma during the pathophysiological progression of CTO vessels and following successful revascularization, moreover, CSF1 and LGALS1 were validated via ELISA. Conclusions The results of this study reveal a dynamic pattern of the molecular response after CTO vessel immediate reperfusion, and identified seven proteins which would be the potential targets for novel therapeutic strategies to prevent coronary CTO.